Numerical Simulation for Rock Fracture Viscoelastic Creep under Dry Conditions - Hao Kang; Herbert Einstein; Stephen Brown; John Germaine (Geofluids)
In many rock engineering projects such as hydrocarbon extraction and geothermal energy utilization, the hydraulic and mechanical behavior of rock fractures significantly affects the safety and profitability of the project. In field conditions, the hydraulic and mechanical behavior of rock fractures changes with time (the rock fractures creep), and this creep is not negligible even under dry conditions. In addition, creep is strongly affected by the rock fracture surface geometry. However, there is not much literature systematically studying the effect of surface geometry on rock fracture creep under dry conditions. This paper presents the results of a numerical study considering the effect of surface geometry on rough fracture viscoelastic deformations. An in-house numerical code has been developed to simulate the viscoelastic deformation of rough fractures. In addition, another numerical code has been developed to generate synthetic rough fracture surfaces by systematically changing the surface roughness parameters: the Hurst exponent, mismatch length, and root mean square roughness. The results indicate that by increasing the Hurst exponent or decreasing the mismatch length or decreasing the root mean square roughness, the fracture mean aperture decreases, and the contact ratio (number of contacting cells/total number of cells) increases faster with time.